2016
DOI: 10.1182/blood-2015-09-667923
|View full text |Cite
|
Sign up to set email alerts
|

Pomalidomide reverses γ-globin silencing through the transcriptional reprogramming of adult hematopoietic progenitors

Abstract: Key Points Pomalidomide selectively targets BCL11A and SOX6 to induce γ-globin synthesis. The mechanism of action of pomalidomide during erythropoiesis is independent of IKZF1 degradation, in contrast to multiple myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 41 publications
(54 reference statements)
2
79
1
Order By: Relevance
“…7,15 Identifying regulators of Hb switching including these genetic variants could provide promising predictors of b-thalassemia severity and therapeutic targets for re-activating HbF production. 15,16 The proposed modes of Hb switching based on current discoveries rely on various epigenetic and transcriptional regulatory factors that could have interacting roles in this developmental event. [17][18][19][20] Recently, leukemia/lymphoma-related factor encoded by zinc finger and BTB domain containing 7A (ZBTB7A [MIM 605878]) was identified as a regulator that represents an alternative mechanism independent of the g-globin repressor BCL11A, as it can occupy g-globin genes directly.…”
Section: ]-Hbg2 [Mim 142250]-hbg1 [Mim 142200]-hbd [Mim 142000]mentioning
confidence: 99%
“…7,15 Identifying regulators of Hb switching including these genetic variants could provide promising predictors of b-thalassemia severity and therapeutic targets for re-activating HbF production. 15,16 The proposed modes of Hb switching based on current discoveries rely on various epigenetic and transcriptional regulatory factors that could have interacting roles in this developmental event. [17][18][19][20] Recently, leukemia/lymphoma-related factor encoded by zinc finger and BTB domain containing 7A (ZBTB7A [MIM 605878]) was identified as a regulator that represents an alternative mechanism independent of the g-globin repressor BCL11A, as it can occupy g-globin genes directly.…”
Section: ]-Hbg2 [Mim 142250]-hbg1 [Mim 142200]-hbd [Mim 142000]mentioning
confidence: 99%
“…Pomalidomide has been recently shown to induce HbF in part by reducing BCL11A transcription (16). We tested the effects of pomalidomide treatment on two HRI-depleted HUDEP2 populations and control HUDEP2 cells.…”
mentioning
confidence: 99%
“…Pomalidomide, a drug currently used to treat multiple myeloma, can induce HbF production by reducing the levels of transcriptional repressors of fetal globin gene expression. 11 In addition, Dulmovits et al showed that pomalidomide was effective in inducing HbF expression in erythroid cells from individuals with and without SCD. 11 A Phase I study of pomalidomide in SCD showed promising results, 12 although a phase II study has not been started.…”
Section: Modulating Haemoglobin F and S Expressionmentioning
confidence: 99%
“…11 In addition, Dulmovits et al showed that pomalidomide was effective in inducing HbF expression in erythroid cells from individuals with and without SCD. 11 A Phase I study of pomalidomide in SCD showed promising results, 12 although a phase II study has not been started. Early phase studies of vorinostat and panibostat are either underway or or complete but have yet to report results.…”
Section: Modulating Haemoglobin F and S Expressionmentioning
confidence: 99%